Exploring the consequence of social media usage on firm performance - Payam Hanafizadeh; Sepideh Shafia; Erik Bohlin (Digital Business, 2021)
This study aims to identify the consequence of social media usage on firm performance. To this end, it proposes a conceptual map that shows promising linkages between the maturity level realization of an organization in social media usage and its corresponding performance consequences. The conceptual map was developed by combining two theories: performance theory and theory of growth and maturity in social media, and then through systematic mapping. This map can predict what performance consequences will emerge in the organization for each stage of maturity in social media usage. According to this conceptual map, the organization is expected to benefit from accessing and sharing knowledge by realizing the first stage of maturity. The realization of the second stage is expected to establish more relationships with the customers, and the third stage will be followed by product and new processes development. By promoting the organization to the fourth stage, it is expected that communication with the organization's stakeholders emerges via social media. In the fifth stage, social media will help with value creation. Thus, managers and professionals can predict what performance consequences they will benefit from if each stage of maturity is realized.
Keywords: 650; Social media; Performance; Systematic mapping; Social media stages of growth model